Serious Games in Radiology Education: Building MR Safety Awareness - Qianhui Cheng; Joanna Pearly Ti; Wai Yung Yu; Hui Ping Oh; Yih Yian Sitoh (The Asia Pacific Scholar, 2022)
Introduction: Magnetic Resonance (MR) safety is critically important in any Radiology Department, and MR-related accidents are preventable. Serious games provide opportunities for learners to build MR safety awareness through play in an immersive learning environment by using simulated scenarios such as screening virtual patients and managing an MR-related accident. Methods: We developed a serious game, in partnership with a game developer, introducing MR safety concepts to learners as they navigate through a virtual 3D Radiology department. Drag-and-drop minigames are incorporated to aid the learner to identify hazards in and around the MR environment. Virtual patients are placed in waiting areas to provide realism, and learners are tasked to screen them as part of MR Safety Screening checks. A simulation of an MR-related accident prompts learners to make decisions or take actions to ensure safety and mitigate further risks during the accident. The learner also role-plays as a Risk Officer to identify the multiple key incidents that led to the accident. These formative assessments, with instantaneous feedback, assesses the learners' knowledge of MR safety. Results: Pilot feedback of this serious game revealed that it is realistic, engaging and relatable. The instructions within the game were clear and aided learning. The game has also been scaled up and customised for the radiology departments of 3 other healthcare institutions. Conclusion: Serious games provide a training solution to raise MR safety awareness by simulating real-life scenarios in an immersive learning environment. It supplements face-to-face training and is scalable to other healthcare institutions.